ANALISIS KONSEKUENSI KEBAKARAN DAN LEDAKAN DENGAN METODE DOWS FIRE AND EXPLOSION INDEX PADA PROYEK SOUTH SIDE APARTEMENT DEPOK TAHUN 2021 - Smart Rusdanarto (2021)
Fire and explosion accident has large impact and difficult to predict. The South Side Apartment project is a construction site that has a diesel tank of 5000 liters. The diesel tank has potential to generate fire and explosion. Therefore, it is important to do a consequence analysis. The aim of this study was to analyze the consequences if fire and explosion occurs in the diesel tank in the South Side Apartment project. This research was a descriptive study using the value of Dows Fire and Explosion Index method. The results of this study obtained the value of Fire and Explosion index of 28.83, so it is included in the light category. The area of exposure is 171.018 m2. Loss control credit factor is 0.873. Maximum Probable Days Outage is 1.7 days, thus resulting business interruption of Rp.138,344,111. Even though the value of fire and explosion index is light, the resulting impact still quite large. The area of exposure was not only affected the project area, but also affects the community area. The loss control credit factor in project area has not been effective. It was suggested that the South Side Apartment project to improve their fire and explosion protection system.